2011
DOI: 10.1155/2011/159541
|View full text |Cite
|
Sign up to set email alerts
|

The Psoas Compartment Block for Hip Surgery: The Past, Present, and Future

Abstract: A posterior lumbar plexus block or psoas compartment block (PCB) is an effective locoregional anesthetic technique for analgesia and anesthesia of the entire lower extremity including the hip. Since the first description in the early seventies, this technique has been modified based on advanced knowledge of the anatomical localization of the lumbar plexus and the improvement of technical equipment. This paper provides an overview of the history, clinical efficacy, and risk profile of the PCB focused on hip sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 48 publications
0
25
0
7
Order By: Relevance
“…The psoas compartment block has been described as analgesically potent as an epidural technique during hip surgery, but reports caution regarding the possibility of severe complications, with the main risk being intrathecal or intravasal application of cardiotoxic doses of local anesthetics. With the advanced use of ultrasound however, these deep blocks may become even safer and their role in an intraoperative setting during hip surgery will have to be further evaluated [19] . Due to the perceived risk involved in epidural, spinal or lumbar plexus blocks under anticoagulants, the femoral block has been developed as a possible alternative and has shown promising results considering postoperative analgesia, but has been criticized as an impediment to early postoperative ambulation [20] .…”
Section: Benefits and Pitfallsmentioning
confidence: 99%
“…The psoas compartment block has been described as analgesically potent as an epidural technique during hip surgery, but reports caution regarding the possibility of severe complications, with the main risk being intrathecal or intravasal application of cardiotoxic doses of local anesthetics. With the advanced use of ultrasound however, these deep blocks may become even safer and their role in an intraoperative setting during hip surgery will have to be further evaluated [19] . Due to the perceived risk involved in epidural, spinal or lumbar plexus blocks under anticoagulants, the femoral block has been developed as a possible alternative and has shown promising results considering postoperative analgesia, but has been criticized as an impediment to early postoperative ambulation [20] .…”
Section: Benefits and Pitfallsmentioning
confidence: 99%
“…Reports of severe complications and familiarity with other techniques may explain the reluctance of anesthesiologists in choosing LPB. However, epidural analgesia has known secondary effects 14 . Our study confirms scarce studies results which conclude that cLPB may provide similar or better analgesia as compared to epidural block, with the advantages of decreasing the incidence of adverse effects 8,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Psoas major muscle is separated into a superficial part and deep part. Psoas compartment exists between the superficial part and the deep part, including lumbar plexus consisted of L1-L4 nerve [8]. Sensory innervation of the hip joint area is composed of obturator nerve and femoral nerve from the lumbar plexus [9].…”
Section: Patients (Association Research Circulation Osseus Classificamentioning
confidence: 99%
“…However, some studies have reported that injection into the adductor muscle has a risk of femoral nerve injury and hematoma [8]. Although psoas major muscle plays an important role as a stabilizer of the hip joint [7], several other muscles and ligaments (iliofemoral ligament, pubofemoral ligament, ischiofemoral ligament) around the hip joint contribute to the stabilization and motion of the hip joint [10].…”
Section: Patients (Association Research Circulation Osseus Classificamentioning
confidence: 99%